Pengaruh Beban Vertikal Terhadap Daya Dukung Lateral Pondasi Tiang - Nugroho, Soewignjo Agus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pile foundations are intended to hold both vertical and horizontal loads. Pile foundation design must take into account the lateral carrying capacity, especially on those that experience large lateral force. In fact, vertical load and horizontal load work simultaneously on the piles. Therefore it is necessary to look at the effect of the vertical load towards the carrying capacity the lateral piles. This study uses several models of pile foundation. The inclination of which the models are varied pile into three kinds, namely the inclination of 0° (upright pole), the inclination of 15o and 30o. While the vertical load is varied into four kinds, namely 0 kg load (no-load), 0,5 kg, 1 kg and 2 kg.The tests were done by inflicting horizontal loading on each variation of test models. Load test results are interpreted using the Tangent Intersection, Davisson method, the Chin method, and Mazurkiewicz method to get the ultimate lateral bearing capacity. The interpretation result of Tangent Intersection method showed the tendency to increase the carrying capacity of the lateral pile models as the vertical load increase. While the results of interpretation met of Chin method, generally showed the same trend. However, the interpretation of Davisson method and Mazurkiewicz methods did not indicate any trend of increasing the lateral carrying capacity with the increase of vertical load. The relationship between the carrying capacity and the inclination of the pile, from the interpretation of the data of load test results, did not indicate a trend of increasing the lateral carrying capacity of the pile models as the inclination of the piles increase.Keywords : pile foundation, model, lateral, vertical load